Determinants for a Successful Interstate Ro-Ro Operations in Indonesia-Malaysia-Thailand: A Review - Amayrol Zakaria; Aminuddin Md Arof (International Journal of Supply Chain Management, 2018)
In accelerating the integration of the Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) and realising more equivalent modal splitting, short sea shipping (SSS) has become a progressively important component in IMT-GT transport planning. Over the years, numerous studies have attempted to look into the SSS requirements and to classify the SSS routes which are economically practicable. Interestingly, Ro-Ro services have become one of the interest areas under the SSS operations that have been extensively researched particularly in Europe. Notwithstanding the efforts made to develop successful Ro-Ro operations, there still exists a great potential which has yet to be exploited enough for various reasons. This paper aims to review the key factors which may contribute to successful Ro-Ro SSS operations. Although a myriad of important factors identified by means of empirical studies, a counter argument is that the important determining factors which are required for a particular route or region may not be applicable to another. In Europe and North America, SSS was introduced to divert road freight transportation away from the congested roads as its main purpose, whereas in Southeast Asian countries, SSS has been part of the initiative to ensure the attainment of a well-connected Association of Southeast Asian Nations (ASEAN) community. However, earlier Ro-Ro operations along some of the routes were not able to sustain and ceased operations after several years. Hence, although important lessons can be learned from the experience of other regions, a more comprehensive study need to be conducted before any Ro-Ro SSS endeavour could be initiated to ensure the important determinants for its success that may be peculiar to a particular region or corridor are identified and addressed.